Economic Importance of Innovative Technologies for Improving Hotel Services - Istamkhuja Olimovich Davronov (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
This article focuses on the economic importance of innovative technologies for improving hotel services. Nowadays we cannot imagine hospitality business without technologies. This article also analyzes how to achieve the goals in competitive market after pandemic periods Today we: people of decade live in the advanced world. Internet known as the Internet, new kinds of devices, gadgets, web-based media networks and other different innovative victories join our entire world. The hospitality business is additionally accepted various sorts of innovations. Each hotel organization has a standard arrangement of technologies for performing continuous tasks and visitors. However, their quality doesn't offer an upper hand. Accordingly, the management of each significant inn is attempting to discover new innovative advancements for their ventures. On the off chance that a couple of years’ prior such technological innovations were related with potential changes in activity without meddling with PC innovation, presently the cycle is without the most recent advancements in the field of informatics. Numerous items show up available, for instance, as mechanized administration frameworks that permit workers to help and make it more productive. For this reason, this study is to characterize the most recent advances and developments just as discovering the best ones for hospitality business Keywords: hospitality industry, service quality, innovations, technologies, gadgets, innovative services, hotel products, economy